2009
DOI: 10.1161/circulationaha.108.796276
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Secular Trends in Elevated Blood Pressure and Obesity in Children and Adolescents in a Rapidly Developing Country

Abstract: Background-The effect of the increasing prevalence of obesity on blood pressure (BP) secular trends is unclear. We analyzed BP and body mass index secular trends between 1998 and 2006 in children and adolescents of the Seychelles, a rapidly developing island state in the African region. Methods and Results-School-based surveys were conducted annually between 1998 and 2006 among all students in 4 school grades (kindergarten and 4th, 7th, and 10th years of compulsory school). We used the Centers for Disease Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
88
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 45 publications
10
88
2
1
Order By: Relevance
“…[24][25][26][27] In the United States, the Bogalusa heart study and the Minneapolis Children's BP Study illustrated a decline in either the SBP or DBP among different groups between the ages of 10 and 17 years, from 1981 to 1992 and 1986 to 1996, respectively. 24,25 In the Seychelles, the mean SBP declined 2.8-3.0 mm Hg in children, whereas the mean DBP did not change in boys, and elevated slightly (0.4 mm Hg) in girls between 1998 and 2006 (Chiolero et al 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] In the United States, the Bogalusa heart study and the Minneapolis Children's BP Study illustrated a decline in either the SBP or DBP among different groups between the ages of 10 and 17 years, from 1981 to 1992 and 1986 to 1996, respectively. 24,25 In the Seychelles, the mean SBP declined 2.8-3.0 mm Hg in children, whereas the mean DBP did not change in boys, and elevated slightly (0.4 mm Hg) in girls between 1998 and 2006 (Chiolero et al 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Thus, the recognition and management of elevated BP at an early age may be an important strategy for limiting the overall disease burden caused by hypertension. 4,5 Factors such as genetics, 6 diet 7 and physical activity 8 appear to contribute to elevated BP in children. In addition, population-based studies have consistently shown that overweight/obese children have higher levels of BP and a higher prevalence of hypertension than their non-overweight/obese counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Thus, the recognition and management of elevated BP at an early age, and the identification of modifiable risk factors, may be an important strategy for limiting the overall public health disease burden caused by hypertension. 4,5 Physical activity is a key component of the therapeutic lifestyle changes recommended for preventing and treating elevated BP and hypertension in children and adolescence. 6,7 There is evidence that levels of physical activity, aerobic fitness and CVD risk factors track from childhood and adolescence into adulthood.…”
Section: Introductionmentioning
confidence: 99%